Power Rates Calculation Monitoring Prototype Electricity Using NODEMCU ESP32 - Muhammad Syafarrudin; Endah Fitriani (SITEKIN: Jurnal Sains, Teknologi dan Industri, 2023)
The use of tools for monitoring electric power rates and controlling the use of electric power rates is urgently needed. Homeowners often leave the electricity. For example,  they use a  refrigerator and a magic jar that is always turned on, which wastes electrical Energy and makes electricity bills expensive. This report aims to create a tool to monitor electric power in real time and calculate the electricity rates used, which users can be controlled on a WebApp. The hardware used is the Pzem-004T sensor, a reader of the overall electric power,  OLED 128x64 as a display of used electric power rates, Proximity as a distance sensor, Push button as a reset button for electric power rates, DS1307 RTC module as time accuracy and S.D. module Card as log data storage and NodeMCU ESP32 as input and output process, by utilizing the wifi from NodeMCU ESP32 as a link between the device and a cellphone or computer to be able to open the WebApp dashboard. On the WebApp dashboard, there is information on recording electricity rates every month, and there are options to reset bills and change billing limit notifications. A message will appear if the account exceeds the limit, and the OLED screen will continue to live. Electricity bill rates are automatically reset every month, and the data will be stored, which can be seen on the WebApp dashboard.